731 Prader Willi Syndrome (PWS) - Particular Molecular Profile and Diagnostic Protocol in Romania. (October 2012) - Simina, IE Jurca-; Gafencu, M; Dan, D; Puiu, M
Abstract : Background and Aims: PWS-a rare genetic disease with a 1/12000–1/15000 newborns frequency, caused by deletion of some genes on paternal origin or maternal disomy of 15'th chromosome. Main clinical manifestations are: neonatal hypotonia, excessive childhood feeding, obesity, cognitive deficiencies. Our aims are to implement molecular genetic/epigenetic tests and to develop interdisciplinary clinical research protocol, which allow early diagnostic and intervention in Romania. Materials and Methods: This study is part of a multicenter research project (CNMP/Partnerships, 2008–2011), on 19 Romanian PWS patients, 12 females, 7 males, between 6 months and 29 years. For diagnostic, were used major and minor criteria (Gunay-Aygun) as clinical methods and 5 genetic tests. Results: All patients have a clinical diagnostic score above 5, 63% of them having a maximal major criteria number with 100% neonatal hypotonia, 95% feeding difficulties at infants and hyperphagia after and a BMI till 60.2kg/cm 2 . 15% of patients have all minor criteria positive, with lethargy at infants, viscous saliva and small extremities predominance. 5% of patients have a positive 15q11–q13 microdeletion, 79% a FISH positive and for 47% patients MS-PCR is positive. Techniques like MS-MLPA were late introduced in Romania, 20% of our patients having them. Conclusions: The study indicates a relative correlation between clinical score and cytogenetic/molecular PWS confirmation and emphasizes the importance of early diagnostic. Interdisciplinary clinical criteria, karyotype, FISH and methylation analysis (MS-PCR, MS-MLPA) are the main steps for a successful diagnostic protocol. Genetic tests results show a particular molecular profile in Romania with only 47% positive methylation results unlike literature (99%).